Correlation of Level of Physical Activity with Weight Perception, Body Mass Index and Body Image Dissatisfaction among Physiotherapy Students of Government Tertiary Care Hospital (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2022)
Background- Obesity has been increasing steadily and is one of the major cause of many noncommunicable diseases among young population. Physiotherapy profession revolves around health and fitness and thus physiotherapy students were chosen for the study. The aim of the study is to find correlation of levels of physical activity with weight perception, body mass index and body image dissatisfaction among physiotherapy students of government tertiary care hospital.Method- It was an observational, cross sectional study of 68 physiotherapy students of either gender between the age of 18-25 years. Perceived weight was documented, body mass index calculated and questionnaires were used to score body image dissatisfaction and physical activity.Conclusion- We found no correlation between level of physical activity and weight perception(p>0.05) and between level of physical activity and Body Image Dissatisfaction (p>0.05). However, there was a correlation between level of physical activity and Body Mass Index with p≤0.05, ρ=0.281. The result highlights the importance of increasing awareness towards self-acceptance of body image and focus on physical activity.
Keywords: Body Image Dissatisfaction, Body Mass Index, Physical activity, Physiotherapy students, Weight perception